Study of engineering properties of vegetable seeds for design of seed dryer - DEVI, THINGUJAM BIDYALAKSHMI; MANI, INDRA (The Indian Journal of Agricultural Sciences, 2017)
A study was carried out to find the effect of moisture content on various engineering properties of carrot, onion and tomato seeds. The range of moisture studied was between 8±1 to 20±1% w.b for all the crop seeds. The bulk density for carrot, onion and tomato increased from 0.32±0.01 g/cm3 to 0.43±0.04 g/cm3, 0.45±0.01 g/cm3 to 0.47 ±0.003 g/cm3 and 0.28±0.01 g/cm3 to 0.30±0.01 g/cm3, respectively when the moisture content decreased from 20±1 to 8±1% wet basis. Sphericity of carrot, onion and tomato decreased by 6.7%, 1.4% and 6% with the increase in moisture content by 60.68%, 58.6% and 60.48% for respectively. The true density and porosity increased for onion and tomato whereas the same decreased for carrot with the decrease in moisture content. All the other engineering properties such as test weight (1000 seed weight), surface area, arithmetic mean diameter, geometric mean diameter and angle of repose increased with the increase in moisture content. The coefficient of friction of all the crops decreased at four different surfaces e.g. wood, mild steel, aluminium and galvanized iron with the increase in moisture content. The regression equations for all the response variables were significant at P<0.05 with coefficient of determination, R2 (>0.90).